The Influence of the 7P Marketing Mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) on Patient Loyalty - Monalisa Putri Eka Berti; Tri Budi Wahyuni Rahardjo; Titus Indrajaya; Siti Maemun; Aninda Dinar Widiantari (GLOBAL HEALTH SCIENCE GROUP, 2026)
The increasing number of hospitals in Jakarta reflects the high demand for healthcare services, which, in turn, may intensify competition. On the other hand, a 15% decrease in the number of returning patients during the 2023–2024 period at the outpatient unit of Sulianti Saroso Hospital indicates low patient loyalty. This study analyzes the relationship between the 7Ps marketing mix and patient loyalty at the outpatient unit of Sulianti Saroso Hospital. A quantitative, cross-sectional design was used, with 110 outpatients as respondents selected via purposive sampling. Data were collected using a valid and reliable questionnaire and analyzed using Chi-Square analysis. The research findings demonstrate a significant relationship between the 7Ps of the marketing mix and customer loyalty. Each element, product (p-value = 0.0001), price (p-value = 0.0001), place (p-value = 0.0001), promotion (p-value = 0.0001), people (p-value = 0.0001), process (p-value = 0.0001), and physical evidence (p-value = 0.0001) shows a statistically significant correlation. The study concludes that all components of the marketing mix positively and significantly influence customer loyalty, with the service process as the most dominant factor.